Methods of working with pharmacovigilance signals - O. A. Loginovskaya; B. K. Romanov; A. S. Kolbin; H. . Yastrebova; K. V. Domoroshchenkov; V. P. Kolbatov; R. V. Sukhov; K. A. Koshechkin (Izdatelstvo OKI, 2018)
This article is about the efficiency of web based systems for pharmacovigilance (PV) processes management in connection with pharmacovigilance signals based on case study of the implementation of Flex Databases PV system. It describes principles of signals management, provides analyses of modern methods of signal management (quality and quantity), and also describes perspective methods of signals management. The article highlights the importance of signal management in pharmacovigilance as an obligatory process for all companies-holders of registration certificate and investigation companies in all EAEU member states, including Russia.